Quantification of Torque Teno Virus (TTV) in plasma and saliva of individuals with liver cirrhosis: a cross sectional study - Falabello de Luca, Ana Clara; Marinho, Gabriella Bueno; Franco, Juliana Bertoldi; Tenório, Jefferson da Rocha; Andrade, Natália Silva; Batista, Alexandre Mendes; Mamana, Ana Carolina; Tozetto-Mendoza, Tânia Regina; Pérez Sayáns, Mário; Braz-Silva, Paulo Henrique; Ortega, Karem L. (Frontiers in Medicine, 2023)
Introduction Torque teno virus (TTV) has been pointed as an endogenous marker of immune function, the objective of this study was to investigate the TTV viral load in plasma and saliva of cirrhotic individuals and correlate it with clinical characteristics. Methods Blood, saliva, clinical data from records and laboratory tests were collected from 72 cirrhotic patients. Plasma and saliva were submitted to real-time polymerase chain reaction for quantification of TTV viral load. Results The majority of the patients presented decompensated cirrhosis (59.7%) and 47.2% had alterations in the white blood series. TTV was identified in 28 specimens of plasma (38.8%) and in 67 specimens of saliva (93.0%), with median values of TTV copies/mL of 90.6 in plasma and 245.14 in saliva. All the patients who were positive for TTV in plasma were also positive in saliva, with both fluids having a moderately positive correlation for the presence of TTV. There was no correlation between TTV viral load, either in plasma or in saliva, and any of the variables studied. Conclusion TTV is more frequently found and in greater amount in the saliva than in the plasma of cirrhotic patients. There was no correlation between TTV viral load and clinical parameters.